2006
DOI: 10.1021/ma051777l
|View full text |Cite
|
Sign up to set email alerts
|

Crystal and Lamella Structure and C−H···OC Hydrogen Bonding of Poly(3-hydroxyalkanoate) Studied by X-ray Diffraction and Infrared Spectroscopy

Abstract: Temperature-dependent X-ray diffraction and infrared (IR) spectra were measured for poly(3-hydroxybutyrate) (PHB) and poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) P(HB-co-HHx) (HHx = 2.5, 3.4, 10.5, and 12 mol %) to explore their crystal and lamella structure and the C−H···OC hydrogen bonding in them. The X-ray diffraction and IR measurements of PHB and P(HB-co-HHx) revealed that the smaller the a lattice parameter, the higher the frequency (∼3008 cm-1) of the C−H stretching band of the C−H···OC hydrogen bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
138
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 115 publications
(147 citation statements)
references
References 26 publications
9
138
0
Order By: Relevance
“…According to our previous IR study, [52][53][54] the unusual high wavenumber shift of the CH3 asymmetric stretching band at 3007 cm -1 indicated the existence of a C-H···O=C hydrogen bond. Moreover, the CH stretching band shifts from 2878 to 2873 cm -1 upon the crystallization (Fig.…”
Section: ·1 Applications To Polymer Science and Engineeringmentioning
confidence: 79%
See 2 more Smart Citations
“…According to our previous IR study, [52][53][54] the unusual high wavenumber shift of the CH3 asymmetric stretching band at 3007 cm -1 indicated the existence of a C-H···O=C hydrogen bond. Moreover, the CH stretching band shifts from 2878 to 2873 cm -1 upon the crystallization (Fig.…”
Section: ·1 Applications To Polymer Science and Engineeringmentioning
confidence: 79%
“…[49][50][51] Figure 4 illustrates the crystal and lamella structure of PHB. Recently, Sato et al [52][53][54] investigated the crystallization and melting behavior of PHB by using wide-angle X-ray diffraction (WAXD), IR spectroscopy, and differential scanning calorimetry (DSC). They found that in the IR spectra of PHB, the crystalline CH3 asymmetric stretching band appears at an anomalously high frequency (3009 cm -1 ), and the crystalline C=O band at 1723 cm -1 shows a downward shift compared with the amorphous C=O stretching band.…”
Section: ·1 Applications To Polymer Science and Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the properties of a polymer are highly dependent on its morphological structure, which in turn results from its processing conditions including crystallization. Hence, the crystallization behavior of PHB was studied by using various techniques, including differential scanning calorimetry (DSC), small-and wide-angle X-ray scattering (SAXS and WAXS), and infrared (IR) spectroscopy (Abe et al, 1998;Capitan et al, 2004;Chiu et al, 1999;Doi et al, 1995;Feng et al, 2002;Gunaratne et al, 2004;Kamiya et al, 1991;Numata et al, 2004;Pearce & Marchessault, 1994;Sato et al, 2006;Sato, Murakami et al, 2004;Sato, Nakamura et al, 2004;Zhang et al, 2005;Scandola et al, 1992). In particular, the SAXS technique has been employed to investigate the morphological structure of PHB already crystallized from the melt (Abe et al, 1998;Capitan et al, 2004;Chiu et al, 1999;Numata et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the SAXS technique has been employed to investigate the morphological structure of PHB already crystallized from the melt (Abe et al, 1998;Capitan et al, 2004;Chiu et al, 1999;Numata et al, 2004). Recent IR spectroscopy studies found that in the lamellar crystals of PHB, there is hydrogen bonding between the methyl group of one helical structure and the carbonyl group of another helical structure along an axis of the crystal lattice, and such hydrogen bonding stabilizes the chain folding in the lamellar crystals (Sato et al, 2006;Sato, Murakami et al, 2004;Sato, Nakamura et al, 2004;Zhang et al, 2005). However, detailed studies on the evolution of morphological structures in this microbial polyester and its crystallization mechanism are still needed.…”
Section: Introductionmentioning
confidence: 99%